Coronary artery surgery: indications and recent experience. Issue 636 (October 1978) - Robinson, P. S.; Coltart, D. J.; Jenkins, B. S.; Webb-Peploe, M. M.; Braimbridge, M. V.; Williams, B. T.
Abstract : The comprehensive experience of coronary artery surgery in a Cardiothoracic Unit over a 31-month period is reviewed. Hospital mortality for elective bypass grafting was 3.9% overall and 2.5% in those with good pre-operative left ventricular function. Major influences on hospital mortality were pre-operative left ventricular function, extent of coronary artery disease and extent of the surgical procedure undertaken in terms of number of aortocoronary grafts inserted, coronary endarterectomy and particularly concomitant valve surgery or aneurysm resection. Follow-up experience shows 74% of grafted patients to be symptom-free and 85% symptomatically improved one year after surgery with 70% symptom-free and 80% improved at two years. Early post-operative deaths appear related to early graft closure and recurrence of symptoms postoperatively to late graft closure or progression of coronary disease in the native circulation. The study provides a guide to the relative risks of coronary artery surgery for symptomatic coronary artery disease and expected symptomatic results in the early follow-up period.